Applying Appreciative Inquiry to Research in the Field of Inclusive Education - Melissa Dockrill Garrett (Canadian Society for Studies in Education, 2022)
Inclusionary educational models affirm that every student can learn. The ever-changing scope of the field of education and the pedagogical practices used to meet the diverse needs in the classroom requires research designs which have the capacity to explore the various facets of the field. This article follows the vein of Action Research and the various designs currently used within educational research. While Participatory Action Research designs and methods typically have a problem-based approach, Appreciative Inquiry reframes such views through a Positive Psychology lens to draw out strengths, promising practices, dreams, and potential innovations in the roles of educators and operational structures for the promotion of student flourishing within the context of inclusionary education. The purpose of this article is to support the increased use of the Appreciative Inquiry research design within current inclusionary education investigations, allowing for active participation, collaboration, co-construction, and an appreciative focus on "what is good" and "what works well" in current practice.